STRATEGIC HUMAN RESOURCE MANAGEMENT AS A FACTOR IN GAINING AN ORGANIZATION’S COMPETITIVE ADVANTAGE - L. Ivanovskaya (Вестник университета, 2017)
This article looks at the nature and characteristic of strategic management of an organization and strategic management of its human resource, and links between them. The article describes objectives and goals that HR management should pursue to gain competitive advantage. It also shows the role of HR function in strategic management, explores the nature of HR management strategy and describes modern approaches to a development of HR management strategy. Finally, this article shows the stages of a development, choice and implementation of HR management strategy.